A hands-on STEAM picture book model to enhance critical thinking and integrated science learning interest of elementary school students - Pande Kadek Ary Wimbawati; I Wayan Kertih; I Wayan Widiana (Psychology, Evaluation, and Technology in Educational Research, 2025)
Critical Thinking and Science Learning Interest among third-grade elementary students are still low due to conventional learning methods that lack active engagement. This research aims to develop and test the feasibility of the Picture Story Book Media with a STEAM approach to enhance both of these dependent variables, focusing on the topic of Unique Relationships in Living Things (Symbiosis). Using the ADDIE Research and Development (R&D) model, the product was tested and achieved Very Valid and Very Practical criteria, confirming its implementation feasibility. The effectiveness results were significant. The increase in Learning Interest was categorized as Very High, particularly in the Active Involvement indicator (Slameto), as the narrative successfully triggered enjoyable hands-on action. Critical Thinking improvement was also categorized as High, specifically in the Interpretation and Analysis dimensions (Facione). This was driven by the Engineering challenge to design symbiosis models, which compelled students to use critical logic. This media successfully integrates Story and Art with Hands-On Activities to transform abstract Symbiosis concepts into solution-based investigations. This product effectively strengthens both students' Critical Thinking and Learning Interest.